Answer:
x = -19
Step-by-step explanation:
Multiply both sides of the equation by -9.
x - 26 = -45
Add 26 to both sides.
x - 26 + 26 = -45 + 26
x = -19
Answer:
(0, - 3 ) and (- 1, - 5 )
Step-by-step explanation:
Given the 2 equations
y = 4x² + 6x - 3 → (1)
y = 2x - 3 → (2)
Substitute y = 4x² + 6x - 3 into (2)
4x² + 6x - 3 = 2x - 3 ( subtract 2x - 3 from both sides )
4x² + 4x = 0 ← factor out 4x from each term
4x(x + 1) = 0
Equate each factor to zero and solve for x
4x = 0 ⇒ x = 0
x + 1 = 0 ⇒ x = - 1
Substitute these values into (2) for corresponding values of y
x = 0 : y = 2(0) - 3 = 0 - 3 = - 3 ⇒ (0, - 3 )
x = - 1 : y = 2(- 1) - 3 = - 2 - 3 = - 5 ⇒ (- 1, - 5 )
Answer:
-1,0, 6.3,
Step-by-step explanation:
if its right mark me brilliant please
Answer:
Step-by-step explanation:
x=0 y=6-2*0=6
x=1 y=6-2*1=4
x=2 y=6-2*2=2
x=3 y=6-2*3=0
6-2x=3
-6 -6
-2x=-3
2x=3
:2 :2
x=3/2
x=1.5